PENGEMBANGAN LKPD BERBASIS KARAKTER MELALUI PENDEKATAN VCT PADA MATERI SILA-SILA PANCASILA KELAS III SEKOLAH DASAR - Chelsy Aimy Palber; Lukman Hakim; Ali Fakhrudin (Universitas Negeri Medan, 2021)
Abstract :Development Of Character Based LKPD Through VCT Approach To The Principles Of Pancasila Materials Class III Elementary School. This development research aims to: Knowing the procedure, validity, practicality (LKPD) based on character through the VCT approach on the material of the Pancasila Precepts for Grade III Elementary School. The method used in this research is R&D with the ADDIE model. This research was conducted at SD Negeri 74 Palembang. Based on the results of the study, it showed that the assessment by material expert 1 scored 86%, material expert 2 scored 92%